Hubungan Antara Beban Kerja Dengan Kejadian Postural Kifosis Pada Pekerja Buruh Gendong Wanita Dipasar Gede Solo Jawatengah - Waryani, Siti; , Maskun Pudjianto, S.MPh, M.Kes (2017)
Background: the job is basically a laborer carrying porters who bring belongings seller or the buyer in traditional markets and industrial areas. The number of workers in Pasar Gede carrying up to 65 women. With the demands of the state of many of them carrying workers to do the job a long time and is less convenient, this causes the spine complaints complaint form kelianan bent posture (kyphosis). Do posture using inspection Flexicurve standards. Objective: To investigate the relationship workload with the incidence of postural kyphosis on the workers carrying. Methods: an observational study with method. cross sectional Technical sampling using purposivesampling.The total sample of 65 people. Primary data obtained from direct observation. The test statistic usingtest. Pearson Chi Square Results: Respondents aged 45-50 years amounted to 7 people (10.8%) had kyphosis, 8 (12.3%) did not kyphosis, at the age of 51 and 55 years of 5 people (7.7%) had kyphosis, 6 people (9.2%) did not kyphosis. Then at the age of 56-60 years amounted to 20 (30.8%) kyphosis and 5 (7.7%) did not kyphosis, At the age of 61-65 years amounted to 12 (18.5%) kyphosis and 2 (3 , 1%) did not kifosis.Data was tested with Pearson Chi Square obtained the value p = 0,025 which means there is a relationship between workload with the incidence of postural kyphosis. Conclusion:There is a relationship between workload with the incidence of postural kyphosis.